Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 1-2 - Cumulative Review - Page 217: 6


$m = \frac{2P-6}{n^{2}}$

Work Step by Step

$P = \frac{1}{2}mn^{2} +3$ $P = \frac{mn^{2}}{2} +3$ $P-3 = \frac{mn^{2}}{2}$ $2(P-3) =mn^{2}$ $2P-6 = mn^{2}$ $m = \frac{2P-6}{n^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.